THE INFLUENCE OF BRAND IMAGE ON CONSUMER PURCHASE DECISIONS FOR KENANGAN COFFEE PRODUCTS - Sholeha, Aprilia Triwiyanti; Terrylina Aryinta Monoarfa, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Kopi Kenangan is one of the brands that is currently popular with various groups, from young people to adults . This study has significant urgency because it has the potential to contribute to the development of the Kopi Kenangan business, provide deeper insights into consumer behavior, and advance knowledge in the field of marketing. By understanding how brand image influences purchasing decisions, companies can take strategic steps to improve their business performance. The purpose of this study is to measure the impact of brand image on consumer purchasing decisions. This study uses a survey method to analyze data from Kopi Kenangan consumers and test the research hypothesis. Through the survey, this study tests the hypothesis that the more positive Kopi Kenangan The higher the brand image , the higher the likelihood of consumer purchasing decisions. The results of this study are expected to help Kopi Kenangan management in developing more effective marketing strategies to increase sales and customer loyalty and can be a reference for further research that discusses similar topics.